Role of hyperhomocysteinemia in proliferative diabetic retinopathy: A case–control study - Prabha Gupta; Deepa John; Grace Rebekah; Sheeja S John (Indian Journal of Ophthalmology, 2018)
Purpose: Hyperhomocysteinemia has been postulated as a potential risk factor for the development and progression of diabetic retinopathy. The aim of this study was to determine the association of hyperhomocysteinemia with proliferative diabetic retinopathy (PDR). Methods: This was a hospital-based, case–control study, conducted at a tertiary care ophthalmic center in South India. Thirty-nine patients with proliferative diabetic retinopathy were enrolled as cases, and 39 age- and gender-matched patients with no diabetic retinopathy (No DR) were enrolled as controls. Fasting serum homocysteine estimation, as well as baseline investigations, were done in all participants. Data regarding demographic profile and risk factors were documented. Data were analyzed using Chi-square test and independent t-test, as appropriate. Results: The prevalence of hyperhomocysteinemia was higher in PDR (59%) compared to “No DR” (48.7%); however, this difference was not statistically significant (P = 0.36). Similarly, the mean serum homocysteine level in cases was higher than in controls, but this was not statistically significant (17.98 + 6.26 μmol/L vs. 17.71 + 8.17 μmol/L; P = 0.87). Longer duration of diabetes, hypertension, anemia, and renal dysfunction were found to be significantly associated with PDR. Conclusion: The prevalence of hyperhomocysteinemia as well as the mean serum levels of homocysteine were found to be higher in the cases with PDR, compared to the controls with No DR, although the difference was not statistically significant. Longer duration of diabetes, hypertension, anemia, and renal dysfunction were significantly associated with PDR.